PENGARUH PROMOSI DI MEDIA SOSIAL DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SKINCARE MS GLOW - Wiwik Putri Wahyu Ningsi; Sri Ekowati (Yayasan Insani Mandiri Santani, 2021)
This study aims to determine the effect of promotion through social media, and word of mouth on the decision to purchase Ms Glow Skincare (Study on FEBI UM Bengkulu Students). This type of research is a survey research with a quantitative approach, the object of this research is FEBI UM Bengkulu students who use Skincare Ms Glow. With the sampling method, namely the non-propability technique, namely the residential sampling technique. The number of respondents in this study was 70 people. The data collection method used a questionnaire. By using analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely test t and test f. The results of this study can be concluded that the promotion variable through social media Skincare Ms Glow has a positive effect on purchasing decisions, word of mouth (WOM) has a positive effect on purchasing decisions.Keywords: Promotion, Social Media, Word Of Mouth, and Purchase Decisions.